2021
DOI: 10.1101/2021.10.02.462877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA amplification in mixed aqueous-organic media: chemical analysis of leading polymerase chain reaction compositions

Abstract: PCR amplification of GC-rich regions often leads to low yield and specificity. Addition of PCR-enhancing compounds is employed in order to overcome these obstacles. PCR-enhancing additives are low molecular polar organic compounds that are included as undisclosed co-solvents in commercial PCR buffers. In the interest of transparency and to permit further optimization by researchers of PCR compositions for challenging amplification problems, we studied eight PCR buffers by GC/MS to identify and quantify their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Other effective cosolvents include isobutyramide, 2-pyrrolidone, sulfolane, tetramethylene sulfoxide, and 1,3-propanediol, 10 with several of these being used as essential components in some of the most popular commercial PCR products� including isobutyramide in the widely used New England Biolabs Q5 high-fidelity polymerase mastermix and 1,3propanediol in multiple Toyobo PCR products. 17 While destabilizing dsDNA template and secondary structures in ssDNA template to improve amplification efficiency and reduce GC bias, these additives significantly reduce the thermostability and activity of the enzymes because DNA polymerases did not evolve in mixed aqueous-organic media. In our earlier work, we found that 1,4-butanediol is highly potent for the amplification of "difficult-to-amplify" templates 10 but deleteriously affects the polymerase itself (Figure S1).…”
Section: ■ Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other effective cosolvents include isobutyramide, 2-pyrrolidone, sulfolane, tetramethylene sulfoxide, and 1,3-propanediol, 10 with several of these being used as essential components in some of the most popular commercial PCR products� including isobutyramide in the widely used New England Biolabs Q5 high-fidelity polymerase mastermix and 1,3propanediol in multiple Toyobo PCR products. 17 While destabilizing dsDNA template and secondary structures in ssDNA template to improve amplification efficiency and reduce GC bias, these additives significantly reduce the thermostability and activity of the enzymes because DNA polymerases did not evolve in mixed aqueous-organic media. In our earlier work, we found that 1,4-butanediol is highly potent for the amplification of "difficult-to-amplify" templates 10 but deleteriously affects the polymerase itself (Figure S1).…”
Section: ■ Discussionmentioning
confidence: 99%
“…PCR-enhancing additives, such as 1,4-butanediol, have been proven to be very effective, even making PCR amplification feasible for intractable templates, but negatively affect the polymerase. Other effective cosolvents include isobutyramide, 2-pyrrolidone, sulfolane, tetramethylene sulfoxide, and 1,3-propanediol, with several of these being used as essential components in some of the most popular commercial PCR productsincluding isobutyramide in the widely used New England Biolabs Q5 high-fidelity polymerase mastermix and 1,3-propanediol in multiple Toyobo PCR products . While destabilizing dsDNA template and secondary structures in ssDNA template to improve amplification efficiency and reduce GC bias, these additives significantly reduce the thermostability and activity of the enzymes because DNA polymerases did not evolve in mixed aqueous-organic media.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations